INTERNALISASI KARAKTER NILAI ASWAJA AN-NAHDLIYAH BERUPA TASAMUH DAN TAWAZUN PADA SISWA MTs MA’ARIF NU KOTA MALANG - Dian Rizky Mandasari Gunawan; Rosichin Mansur; Bahroin Budiya (VICRATINA, 2022)
Internalization is an effort made to insert values into the soul of the individual so that it becomes his. While the characters are psychological traits, morals, and manners that distinguish one person from another. Internalization of character education through knowledge that is taught only with definitions, concepts related to character, so that character growth is not perfect because nowadays knowledge is balanced with habituation so that character can be embedded properly. Tasamuh's value is being tolerant. And tawazun is balance. ASWAJA education is a conscious and planned effort and interrelationship carried out to believe, instill and practice self-awareness to students. Teachers of Madrasah Tsanawiyah Maarif NU Malang City play an active role in internalizing or instilling the character values of Aswaja An-Nahdliyah in the form of tasamuh and tawazun (tolerance and balance) in students. As for the problems in the new normal era after the easing of the covid 19 virus which had a big impact after online school took place. So when offline schools make students have to re-implant their characters, especially in the form of tasamuh and tawazunya. This study uses a qualitative approach with the type of case study that produces descriptive data from information sources effectively. The researcher concludes that the internalization of ASWAJA's character values in the form of tasamuh and tawazun uses in-class learning and habituation in the school environment.